Strategi Optimasi Promosi Dalam Upaya Peningkatan Investasi Swasta Di Kabupaten Bogor (Jurnal Manajemen Pembangunan Daerah, 2024)
ABSTRACT            The increasing competition among regions underscores the importance of promotion in boosting private investment. The expansive and scattered nature of Bogor Regency necessitates the use of appropriate means to introduce the regency. The research objective of this thesis is to develop promotion development strategies to enhance private investment in Bogor Regency. The method employed in this research is the Analytic Network Process (ANP). The results of the ANP method indicate that the alternative strategy with the highest priority is the focused and directed management of promotion programs, with a value of 0.549. The second priority is the strategy of developing promotional products according to investment potential, with a value of 0.324, and the strategy of improving the quality of human resources in marketing communication is the next priority with a value of 0.128.Keywords: Analytic Network Process, Private Investment, Promotion, Strategy